Transformasi Pembelajaran di Era Digital - Sitanggang, Mutiara Miyagi; Sitopu, Juliaman; Suhardini, Atika; Hasyim, Hasyim; Hutasuhut, Saidun (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The transformation of learning in the digital era has significantly altered educational methods and strategies. Digital technology provides various platforms and tools that enable learning to be more interactive, personalized, and flexible. This article explores how this transformation affects the roles of teachers and students, learning methods, and the challenges faced in its implementation. Using an analytical approach, the article examines the impact of technology on learning effectiveness and its long-term implications for the quality of education.